2008
DOI: 10.1089/fpd.2007.0054
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Detection of Campylobacter lanienae in Fecal Matter and Stored Manure from Swine and Dairy Cattle

Abstract: Tracking sources of contamination is an issue related to food safety. In a preliminary study conducted to evaluate the distribution of thermophilic Campylobacter in the environment surrounding dairy cattle and swine production, a number of Campylobacter lanienae were directly detected by PCR. The amplicons came from dairy cows and pig fecal samples, as well as from stored manure. DNA sequencing of a 360-bp fragment of C. lanienae 16S rRNA gene was performed. Alignment of sequences confirmed the bacterial ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 10 publications
3
20
1
Order By: Relevance
“…The prevalence of Campylobacter in cattle varies significantly across studies, with rates ranging from 23% to close to 90% (333)(334)(335). The species detected in cattle include C. jejuni, C. coli, C. lari, and C. lanienae (335)(336)(337).…”
Section: Domesticated Animalsmentioning
confidence: 99%
“…The prevalence of Campylobacter in cattle varies significantly across studies, with rates ranging from 23% to close to 90% (333)(334)(335). The species detected in cattle include C. jejuni, C. coli, C. lari, and C. lanienae (335)(336)(337).…”
Section: Domesticated Animalsmentioning
confidence: 99%
“…The prevalence in cattle ranges between 19% and 93% using cultural methods, and between 21% and 90% with culture-independent PCR methodology (Table 1). While C. jejuni and C. coli were reported to be the dominant species in cattle manure in most of the culture-based studies (Munroe et al 1983;Waltner-Toews et al 1986;Van Donkersgoed et al 1990b, 2009Inglis et al 2006;Hannon et al 2009a), studies using culture-independent methods indicate that C. lanienae is the dominant species (Inglis et al 2003(Inglis et al , 2004Guévremont et al 2008). This latter species is currently considered to be an emerging cause of enteritis with unknown significance.…”
Section: Cattle and Sheepmentioning
confidence: 99%
“…Provincial surveys using culture methods have found a prevalence of up to 99% (Mafu et al 1989;Varela et al 2007), with C. coli as the most common species detected. Using a PCR method, a survey in Quebec found a prevalence of 25% (Guévremont et al 2008), with 40% for both C. lanienae and C. coli among the positive samples (Guévremont et al 2008). Variability in prevalence appears to be largely associated with source of the samples, with rectal and cecal samples showing higher prevalence than tissue or fecal samples.…”
Section: Swinementioning
confidence: 99%
“…This species was discovered during a routine screen of healthy abattoir workers (Logan et al, 2000), and so far, it has not been associated with human disease. It usually appears in the gastrointestinal tract of food animals such as cattle and swine, although debate exists regarding the main reservoir (Sasaki et al, 2003;Inglis et al, 2004;Guevremont et al, 2008). Guevremont et al (2008) reported a 5 nt difference between C. lanienae strains from pig and dairy cattle in the 5¢ region of the 16S rRNA gene sequence.…”
mentioning
confidence: 99%
“…It usually appears in the gastrointestinal tract of food animals such as cattle and swine, although debate exists regarding the main reservoir (Sasaki et al, 2003;Inglis et al, 2004;Guevremont et al, 2008). Guevremont et al (2008) reported a 5 nt difference between C. lanienae strains from pig and dairy cattle in the 5¢ region of the 16S rRNA gene sequence. Here, sheep isolate C0292-Sh shared its pattern with the bovine sequences.…”
mentioning
confidence: 99%